PENDAMPINGAN LATIHAN LITERASI TAHSIN AL-QUR’AN BAGI ANAK-ANAK DI RUMAH TAHFIDZ BAYT AL-QUR’AN BLIMBING LAMONGAN - Arif Luqman Hakim (Bulletin of Community Service and Development, 2021)
Purpose of the study: The purpose of this activity is to increase the understanding of tahsin al-Qur’an literacy of Bayt Al-Qur’an students in Blimbing, Lamongan. Methodology: The method used is mentoring which includes socialization, training, practice, monitoring, and evaluation. Main Findings: The students at Bayt Al-Qur'an don’tt fully have an understanding yet of Al-Qur'an Tahsin Literacy, with this training there is an increase in the understanding of al-qur'an literacy in students. Applications of this study: This service is useful for the students of Bayt Al-Qur'an to improve understanding of literacy in tahsin al-Qur'an. Novelty/Originality of this study: By using socialization, training, practice, monitoring, and evaluation of tahsin al-Qur'an literacy training, it increases students' understanding of tahsin al-Qur'an.